An empirical analysis of self-enforcement mechanisms: evidence from hotel franchising - Kosova,R; Sertsios,G (Management Science, 2018)
The relational contracts literature suggests that a principal can improve contract self-enforceability by specifying initial requirements that increase the agent’s ex-post rents. Initial requirements specified in hotel franchise agreements — size and quality-tier of hotel — offer a unique empirical setting to test this. Using proprietary data on 5,547 new franchised hotels and their revenues, we find that hotels far away from their franchisor’s headquarters are larger, more likely to belong to a high-quality tier, and generate higher revenues ex-post. This supports the idea that the agent’s ex-post rents can serve as a substitute to the principal’s monitoring intensity in the mitigation of agency problems. Our findings shed light on how formal contract terms can influence informal (relational) contracts between business partners.